The Bibliometric Analysis of the Sunda Pangolin (Manis javanica Desmarest, 1822) Ecological Research in Indonesia - Rianti, Anita; Kwatrina, Rozza Tri; Santosa, Yanto (Media Konservasi, 2024)
Illegal wild animal trade is a conservation threat, predominantly in Indonesia. Most of the animals traded is the pangolin which almost all parts of the body are used, especially the scales. This research used a bibliometric review that uses Scopus, The Web of Science platform, and Google Scholar to analyze publications for one decade to map trends and gaps in pangolin research. The result of this research showed that the total of publications significantly increased over several decades, but the topic for pangolin research is not learned in the same proportion (only 37% of them discussed the population appraisal of pangolin in the wild, the remainder mostly discussed status and conservation of pangolin in 41%, and the effect of illegal pouching and trading in 22%). There is an inconsistency between the researchers in developed countries and developing countries where more research is conducted in developed countries than in developing countries. The data from the analysis research collected systematically in developing countries were not published proficiently, therefore it caused several publications to fall into the grey literature category. There are some research gaps, which are research topics are not diverse and have too many things in common, other than that the population data are not aligned with the biodiversity distribution and conservation priorities, especially concerning endangered species such as pangolins. The success of conservation relied on the policymakers and practitioners, and the implications of this research gave suggestions for the management to overcome the pangolin trade polemic that has become increasingly widespread recently.